Alternate Wavelength Switching in a Widely Tunable Dual-Wavelength Tm $^{3+}$ -Doped Fiber Laser at 1900 nm - Chenglai Jia (IEEE Photonics Journal, 2015)
We demonstrate alternate wavelength switching in a widely tunable, dual-wavelength Tm3+-doped fiber laser operating at 1900 nm. A comb filter based on a Sagnac loop incorporating a length of high-birefringence fiber is used to define the lasing wavelengths. By simple variation of a polarization controller within the laser cavity, alternate and sequential switching between single- and dual-wavelength output, as well as tunable operation over a range of 70 nm, is obtained.